2007
DOI: 10.1371/journal.pmed.0040248
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Impairs Host Defense in Gram-Negative Sepsis Caused by Burkholderia pseudomallei (Melioidosis)

Abstract: BackgroundToll-like receptors (TLRs) are essential in host defense against pathogens by virtue of their capacity to detect microbes and initiate the immune response. TLR2 is seen as the most important receptor for gram-positive bacteria, while TLR4 is regarded as the gram-negative TLR. Melioidosis is a severe infection caused by the gram-negative bacterium, Burkholderia pseudomallei, that is endemic in Southeast Asia. We aimed to characterize the expression and function of TLRs in septic melioidosis.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
218
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(243 citation statements)
references
References 54 publications
19
218
6
Order By: Relevance
“…Wang et al (59) observed that the HO-1/CO pathway is able to suppress LPS-induced TLR4 signaling, including the production of TNF-a and IL-6 in murine macrophages, by regulating the interaction of TLR4 with caveolin-1. Whereas both TLR4 and TLR2 have been found to contribute to cellular responsiveness to B. pseudomallei in vitro, only TLR2 might have an impact on the immune response of the intact host in vivo (60).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (59) observed that the HO-1/CO pathway is able to suppress LPS-induced TLR4 signaling, including the production of TNF-a and IL-6 in murine macrophages, by regulating the interaction of TLR4 with caveolin-1. Whereas both TLR4 and TLR2 have been found to contribute to cellular responsiveness to B. pseudomallei in vitro, only TLR2 might have an impact on the immune response of the intact host in vivo (60).…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of TLRs have been extensively investigated in B. pseudomallei infection, it is still controversial whether TLR2 or TLR4 or the combination of both is involved in triggering host cells. Wiersinga et al used HEK293 cells stably transfected with TLR2/ CD14 or TLR4/CD14 to show that the LPS isolated from B. pseudomallei signals only through TLR2 (35). Moreover, TLR2-deficient mice infected with B. pseudomallei display decreased bacterial loads and prolonged survival, suggesting that TLR2 is essential in B. pseudomallei infection (35).…”
Section: Discussionmentioning
confidence: 99%
“…Wiersinga et al used HEK293 cells stably transfected with TLR2/ CD14 or TLR4/CD14 to show that the LPS isolated from B. pseudomallei signals only through TLR2 (35). Moreover, TLR2-deficient mice infected with B. pseudomallei display decreased bacterial loads and prolonged survival, suggesting that TLR2 is essential in B. pseudomallei infection (35). In contrast, West et al showed that tumor necrosis factor alpha (TNF-␣) production was decreased in LPS-treated TLR4 Ϫ/Ϫ primary macrophages, indicating that TLR4 is involved in proinflammatory cytokine production (34).…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar macrophages were harvested from IRAK-M -/-and WT mice by bronchoalveolar lavage (BAL) (n = 8 per strain) as described (15,16 (19). Labeled bacteria were incubated with macrophages for 1 h at 37°C (MOI 100:1) and cells were analyzed using FACSCalibur (Becton Dickinson, Breda, the Netherlands).…”
Section: Stimulation Of Primary Alveolar Macrophagesmentioning
confidence: 99%